(untitled) (Research, Society and Development, 2022)
Studies on the correlation between hypertension and work are insufficient to provide a picture of the risks to which they are subject on a daily basis. The literature review was conducted through a scientific database search. Objective: To synthesize what is available in the literature about the correlation between the work environment and the development of arterial hypertension. Methodology: The following question was projected on the topic: What studies already carried out, on the correlation of the work environment, managed to define about its effects on the development of arterial hypertension? To research this review, an online search was performed in the following databases: CAPES, CENTRAL, SciELO, BVS, MEDLINE, Academic Google, LILACS and Redalyc. Results: 23 articles were selected, between January 2016 and December 2021, which indicate that the factors: therapeutic regimen; socioeconomic and demographic aspects; relationship with health services and professionals; psychosocial and cultural aspects; and family and social support, focus on the development of hypertension. Discussion: Hypertension is a silent disease and difficult to diagnose, with a higher prevalence in adults, which leads to loss of production with negative consequences for the server and the institution. Conclusion: Studies show that the environment where the worker is, the workload and the work shift significantly influence the emergence of arterial hypertension. Identifying the profile of hypertension is intended to plan preventive actions that can improve these conditions.